Сказки. Рассказы. Повести: [для среднего школьного возраста] / Л. Н. Толстой ; художник Ольга Ким - Толстой Лев Николаевич (Серия "Школьная библиотека", 2021)
Экземпляры: (20220408) / Инвентарный номер: 62970 / Цена: 86.00 / Сис.шифр: Р1ср / Авт.знак: Т 53 / ГРНТИ: 17.82.32 / ББК: 84(2Рос=Рус)1